2024
DOI: 10.1590/1519-6984.253868
|View full text |Cite
|
Sign up to set email alerts
|

Lernaeid parasites prevalence in commercial freshwater fish species at various fish farms in Pakistan

Abstract: Reports abound on Lernaea parasitizing the brood stock, fingerlings, and marketable-sized culturable freshwater fish species in various parts of the world. We investigated seven small-scale aquaculture farms and how the prevailing Lernaea is impacting them. Randomly seven fish farms were selected to determine the prevalence percentage of lernaeid ectoparasites. Relevant information of the fishponds to estimate the various aspects such as effects of water source and quality, feed, stocking density, treatment us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The results of the present study showed that Lernaea cyprinacea has a higher prevalence in L. catla (41.30%) as compared to the other fishes (L. rohita and C. mrigala) present in the same ponds. The results were agreed with Tasawar et al [20] who reported 96 infected L. catla fish samples (prevalence 80%) out of 120, and Bilal et al [21] who reported 60 infected L. catla fish samples (prevalence 41.7%) out of 144. Apart from this Abbas et al [22] reported the highest number of Lernaea (100) in L. catla, and Aslam et al [23] showed more prevalence of Lernaied parasite in Indian Major Carp.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study showed that Lernaea cyprinacea has a higher prevalence in L. catla (41.30%) as compared to the other fishes (L. rohita and C. mrigala) present in the same ponds. The results were agreed with Tasawar et al [20] who reported 96 infected L. catla fish samples (prevalence 80%) out of 120, and Bilal et al [21] who reported 60 infected L. catla fish samples (prevalence 41.7%) out of 144. Apart from this Abbas et al [22] reported the highest number of Lernaea (100) in L. catla, and Aslam et al [23] showed more prevalence of Lernaied parasite in Indian Major Carp.…”
Section: Discussionsupporting
confidence: 91%
“…The pH, oxygen, temperature, and salinity values were within the anticipated range [ 38 , 39 ]. Along with stocking density, climatic factors, and environmental conditions play a significant role in the prevalence of Lernaeid ectoparasites at various geographic locations [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic infection is a common illness affecting freshwater ornamental fishes. Parasites in fish may impede development and cause death, resulting in decreased fecundity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The parasite Laernaea cyprineace is most abundant and harmful among the members of the family Larnaea. (Bilal et al, 2021). The Lernaeid are the sh parasites that belong to the main group of Crustacea (Copepoda).…”
mentioning
confidence: 99%